EFFECT OF NEW PREPARATIONS ON COTTON YIELD COMPONENTS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The application of new preparations in cotton cultivation plays a crucial role in optimizing growth, development, and yield. This study evaluates the effects of biostimulants "Avangard Start," "Gulliver," and the insecticide "Antikolorad Max" on the yield components of cotton (Gossypium hirsutum L.), particularly in meadow soils. The experiment was conducted using the S-8296 cotton variety, comparing different application rates and combinations of these physiologically active substances. The results indicate that the foliar application of these preparations significantly enhances plant growth parameters, increasing boll formation, flower retention, and overall yield. Individually, "Gulliver" and "Avangard Start" demonstrated the most pronounced effects, with "Avangard Start" increasing boll count to 6.7 and open cotton yield to 6.3. Combined applications, such as "Gulliver + Avangard Start + Antikolorad Max," also contributed positively, but in some cases, individual treatments showed superior performance. The findings confirm that targeted use of biostimulants and insecticides can improve cotton productivity by 10–15%, enhance resistance to environmental stress, and optimize nutrient absorption. The study highlights the importance of integrating foliar-applied fertilizers and biostimulants into modern cotton cultivation to ensure sustainable yield improvements.